2016
DOI: 10.1116/1.4955152
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable device isolation by inert gas heavy ion implantation in AlGaN/GaN HEMTs on Si

Abstract: Multiple energies of heavy ion implantation with inert-gas ion (84Kr+) were carried out on AlGaN/GaN high-electron-mobility transistors (HEMTs) for planar device isolation. Thermal stability of the implantated samples were also investigated by isochronal annealing at 500, 600, 700, and 800 °C (each temperature for 1 h.). Due to the damages created by heavy ions (84Kr+) in the GaN lattice, the implant-isolated Al0.27Ga0.73N/GaN HEMT samples exhibited better thermal stability than 40Ar+-implant-isolation. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The observation of enhanced BV gd from implant-isolated HEMT is due to the low gate leakage current. Similar observation has also been realized in AlGaN/GaN HEMTs by Ar þ and Kr þ implantation [5]. P. Liu et al, observed an elimination of gate leakage by placing plasma enhanced tetraethylorthosilicate (PE-TEOS) oxide spacers in between gate and mesa sidewalls [25].…”
Section: Originalsupporting
confidence: 65%
See 2 more Smart Citations
“…The observation of enhanced BV gd from implant-isolated HEMT is due to the low gate leakage current. Similar observation has also been realized in AlGaN/GaN HEMTs by Ar þ and Kr þ implantation [5]. P. Liu et al, observed an elimination of gate leakage by placing plasma enhanced tetraethylorthosilicate (PE-TEOS) oxide spacers in between gate and mesa sidewalls [25].…”
Section: Originalsupporting
confidence: 65%
“…Inter‐device isolation of AlGaN/GaN HEMTs is typically achieved by mesa etching techniques using inductively coupled plasma (ICP) or reactive ion etching (RIE) and BCl 3 /Cl 2 as plasma source. Due to the presence of mesa sidewall in the conventional mesa‐isolation process, the metal gate as well as the passivation layer are in contact with 2‐dimensional electron gas (2DEG) of AlGaN/GaN HEMT structure, which leads to higher gate leakage current and non‐uniformity in buffer breakdown voltage with passivation layer . Moreover, the AlGaN/GaN wafer after mesa‐isolation exhibits a non‐planar surface, which in return affects the process yield of device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 After the implantation, an almost uniform depth distribution of hydrostatic strain in the Al x Ga 1-x N layers the most correctly describes the Al x Ga 1-x N peaks on the (0002) 2θ/ω scan. This is despite the high implantation energy (100 keV) that should have resulted in the maximum concentration of Ar + at the depth of about 90 nm from the surface [19], which is often reported for ion implantation into single crystals [26]. The strain in the GaN buffer increases only after the implantation with the first dose of Ar + ions and is not affected by the second dose.…”
Section: Resultsmentioning
confidence: 91%
“…However, these diodes require the processing of guard rings to avoid the presence of the high electric field under the Schottky contact causing the early breakdown of the diodes. Implantation of many species such as B , Mg , Mg/P , Kr, and Ar have been studied to achieve those guard rings. Good results were achieved with an Mg implantation step and a high temperature annealing, above 1100 °C, to create and activate p‐type doped guard rings .…”
Section: Introductionmentioning
confidence: 99%